Measurement of oxygen chemical diffusion in PuO2‐x and analysis of oxygen diffusion in PuO2‐x and (Pu, U)O2‐x. Issue 2 (18th December 2012) - Kato, Masato; Uchida, Teppei; Sunaoshi, Takeo; Stanek, Christopher R.; Nikl, Martin; Kovács, László; Greulich‐Weber, Siegmund
Abstract Oxygen chemical diffusion in PuO2‐x was investigated in the temperature range of 1473‐1873 K by thermogravimetry as functions of oxygen‐to‐metal (O/M) ratios and temperatures. The oxygen chemical diffusion coefficients, <![CDATA[$ \tilde D $]]> <inline-graphic xlink:href="ark:/27927/pgh6nd00c7" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> were determined assuming that the reduction curves were dominated by a diffusion process. The O/M ratio and Pu content dependence on the chemical diffusion coefficients were evaluated. The chemical diffusion coefficient had its minimum value at around O/M=1.98 and decreased with increasing Pu content in (U, Pu)O2‐x. The self‐diffusion coefficients were evaluated. A model for describing the relationship among O/M ratio, oxygen chemical diffusion, and self‐diffusion was proposed based on defect chemistry. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)